A new species of treehopper in the genus Cladonota Stål (Hemiptera: Membracidae: Membracinae: Hypsoprorini) from Costa Rica, with preliminary observations of its behaviour and natural history - England, Sam J.; Flynn, Dawn J.; Robert, Daniel (Zootaxa, 2020)
Cladonota Stål is a genus of Neotropical treehopper found throughout much of South America, Central America, and as far north as Mexico (Godoy et al. 2006). Whilst many membracids are known to exhibit extravagant pronotal expansions (Buckton 1903), the morphologies found within Cladonota are arguably some of the most extreme, making them a particularly charismatic taxon. The function most frequently proposed for the shape of the Cladonota pronotum is camouflage; in particular, masquerade mimicry of dry leaf or bark fragments (Godoy et al. 2006; Swing 2012). However, this mimetic function remains to be empirically tested.